Pengukuran Ranah Afektif Mata Pelajaran Pendidikan Agama Islam Dalam Penilaian Berbasis Kelas - Mantau, Barhanudinn AK (Jurnal Pelangi Ilmu, 2009)
Affective domain is domain related to attitude and value, attitude is one of psychology area term relating to perception and behaviour. The figures divide level of its interest into five level that is; recognition (receiving), response giving (responding), appreciation to value (valuing), organization (organization), and deed (characterization). Each interest haves the character of hierarchical. For every subject in school has affective indicator measured by teacher, so do education subject of Islam prioritizing expansion of affective domain, for the reason the affective indicator domain must be measured by using some scales that is Iikert double helix scale, scale thurstone, scale diperensial, measurement scale of enthusiasm and attitude scale.